Comparison of work efficiency in factory workers: pre & post covid lockdown - a cross sectional study - Prathamesh Kotagi; Mubashir Angolkar; Rajashree Koppad (BMC, 2023)
Abstract Background The COVID-19 pandemic's impact on economies worldwide has caused changes in work patterns, reduced productivity, and job losses, particularly affecting factory workers. Lockdown measures have also led to reduced physical activity levels, which is a significant risk factor for chronic diseases. This study aims to investigate efficiency of factory workers pre and post lockdown periods. The findings will contribute to identifying evidence-based strategies to minimize the negative impact of lockdown measures on factory workers' productivity and health. Materials and methods A cross-sectional study was conducted to assess the work performance of employees in a medicine manufacturing unit. Data was collected from factory workers online and study period was January 2021 to April 2022. Survey includes close ended questions regarding work performance of employees before lockdown period (Before 20/03/2020) and performance after lockdown period (After August 2020). The sample size of 196 employees selected through simple random sampling. A questionnaire consisting of demographic factors, work details, and work performance was prepared using pretested standard tools, including the Individual Work Performance Questionnaire (IWPQ), the World Health Organization Health and Work Performance Questionnaire (HPQ), and the Stanford Presenteeism Scale (SPS-6). The collected data was analysed using descriptive statistics and a paired t-test. Results The study found that prior to lockdown, 99% of employees consistently had higher performance, with 71.4% ranking in the top 10. However, after lockdown, the percentage of employees with high performance decreased to 91.8%, with only 63.3% ranking in the top 10. These differences were statistically significant, indicating a decrease in work efficiency of 8.1%. Before lockdown, employees worked longer hours, including on off days, while after lockdown, a small proportion missed work due to various reasons, resulting in better quality work. Conclusion In conclusion, the study highlights the significant impact of the COVID-19 pandemic on the work efficiency of factory workers. The findings indicate a decrease in work efficiency after the lockdown, coupled with an increase in employee stress. This suggests that the pandemic has brought about unique challenges for factory workers that need to be addressed to maintain their well-being and productivity. This study emphasizes the importance of creating a supportive work environment that prioritizes the mental and physical health of employees, especially during times of crisis.